2021
DOI: 10.3390/atmos12111453
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Hygrometric Variability on Waterfronts in Negative Radiation Balance: A Case Study of Balneário Camboriú/SC, Brazil

Abstract: Extensive urbanization around the world has resulted in the consumption of massive vegetated areas and natural resources. To this end, one strategy for urban development is to consolidate urban areas. In Balneário Camboriú/SC, Brazil, this trend has transformed the city into a vertical built-up area on its coastal strip, accommodating a large amount of buildings both in terms of quantity and number of floors. This research aims to quantify the thermo-hygrometric fluctuation on the waterfront of Balneário Cambo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 99 publications
0
15
0
Order By: Relevance
“…e = 0.004 * Pv + 0.986 (5) in which NIR refers to band 5 and RED to band 4 of the Operational Terra Imager (OLI) from the Landsat 8 satellite, as mentioned, after passed through atmospheric, topographic corrections and panchromatic sharpening.…”
Section: Land Surface Temperature Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…e = 0.004 * Pv + 0.986 (5) in which NIR refers to band 5 and RED to band 4 of the Operational Terra Imager (OLI) from the Landsat 8 satellite, as mentioned, after passed through atmospheric, topographic corrections and panchromatic sharpening.…”
Section: Land Surface Temperature Estimationmentioning
confidence: 99%
“…Cities are the most evident form of transformation of the natural landscape. The change in the elements of the climate has great ecological repercussions as it immediately affects the inhabitants through thermal discomfort and the concentration of pollutants [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Urbanization is a complex process characterized by the transformation of natural land cover types (e.g., vegetation, water bodies, forests, and croplands) to impervious surfaces, such as roads, buildings, pavements, and parking lots [12,13]. Previous studies have confirmed that impervious surfaces can absorb and retain heat, resulting in higher surface temperatures in urban areas [2].…”
Section: Introductionmentioning
confidence: 99%
“…The selected locations represent the most diverse features of the city that influence the urban climate, including urban geometry, land cover, areas with high verticalization and areas with low verticalization, and distance from the city's boundaries [14,21].…”
Section: Measuring Devicesmentioning
confidence: 99%
“…In order to advance research on LCZs and UHI [14], especially in southern Brazil, this study analyses the formation of urban heat islands throughout the daytime and nighttime in the city of Balneário Camboriú, Santa Catarina, Brazil, from 14 October 2020 to 22 October 2020, from the perspective of the local climatic zones (LCZ) (Spring in the Southern Hemisphere).…”
Section: Introductionmentioning
confidence: 99%